The executive regulations of the value added tax law no. 67 of the year 2016 = اللائحة التنفيذية لقانون الضريبة على القيمة المضافة - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
P1 Definitions -- P2 Value added tax, Ch1 Tax imposition and maturity -- Ch2 Value -- Ch3 Invoices, tax returns, notices, books and records -- Ch4 Registration -- Ch5 Tax deduction, exemption and refund --Ch6 Tax collection, P3 Schedule tax -- P4 General provisions, control and appellate procedures, Ch1 General provisions -- Ch2 Control -- Ch3 Appellate procedures